MEMBENTUK KARAKTER ANAK SEBAGAI GENERASI PENERUS BANGSA MELALUI PENDIDIKAN ANAK USIA DINI - I KETUT SUDARSANA (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2017)
Early Childhood Education, which is one form of the provision of education with emphasis on laying the foundation toward growth and physical development (coordination of fine and gross motor), intellect (the intellect, creativity, emotional intelligence, spiritual intelligence), socioemotional (attitude and behavior and religion), language, and communication, according to the uniqueness and the developmental stages through which early childhood. Therefore, the Early Childhood Education plays an important role in children's education. Through the Early Childhood Education, a child can be educated by teachers with clear methods and curriculum. Children can play and channeling energy through physical activity, music, or hand skills. But they can also learn to interact in interpersonal and intrapersonal. Children can gradually be introduced letters or reading, the environment, agriculture and even industry. The introduction was not excessive, since the delivery tailored to the child's world, the world of play so that the learning process fun. Children are often expressing ideas and feelings through play, so when children feel enjoyed and were happy with what was taught it, then by itself would be beneficial for their development.